The economics of industrial water use - Renzetti, Steven (Cheltenham, UK ; Northampton, MA, USA : Elgar, 2002)
This book presents a collection of significant articles to have applied economic models and measurement techniques to the topic of industrial water use since 1970.
Includes bibliographical references and index.
oif 16/09/15
Loan
Keywords: Industrial water supply -- Economic aspects; Water use -- Economic aspects; Water consumption -- Economic aspects; Industrial water supply